An assessment of ankle stability in elite rugby union - Greene, A. J. (ISBS Proceedings Archive (Michigan), 2020)
The aim of the study was to assess dynamic postural stability and the perceived chronic ankle instability (CAI) in a population of elite rugby union players, and to examine the relationship between these two measures. Thirty-three professional rugby players undertook the Cumberland Ankle Instability Tool (CAIT) as well as dynamic postural control testing using the Y-balance test (YBT). Significant differences of between-limb performance in the posterolateral direction on the YBT were seen for those athletes reporting perceived CAI in one or both ankles when compared to no perceived CAI (p = 0.00). These findings suggest poorer lateral dynamic postural control at the ankle in those athletes who identify as having CAI. By administering these tools together, the study suggests that we are able to identify athletes who may benefit from targeted intervention programs to address compromised ankle stability and potential CAI progression.